Equid infective Theileria cluster in distinct 18S rRNA gene clades comprising multiple taxa with unusually broad mammalian host ranges - Bishop, Richard P.; Kappmeyer, L.S.; Onzere, C.K.; Odongo, David O.; Githaka, Naftaly W.; Sears, K.P.; Knowles, Donald P.; Fry, L.M. (Springer, 2020)
Equine theileriosis, a tick-transmitted disease caused by the hemoprotozoan parasites Theileria equi and Theileria haneyi, affects equids throughout tropical and subtropical regions of the world. It is a significant regulatory concern in non-endemic countries, where testing for equine theileriosis is required prior to horse import to prevent parasite entry. Within endemic areas, infection causes significant morbidity and mortality, leading to economic losses. No vaccine for equine theileriosis is available, and current drug treatment protocols are inconsistent and associated with significant side effects. Recent work has revealed substantial genetic variability among equine theileriosis organisms, and analysis of ribosomal DNA from affected animals around the world indicates that the organisms can be grouped into five distinct clades. As these diverse parasites are capable of infecting a wide range of both tick and mammalian hosts, movement of different equine Theileria species between endemic countries, and eventually into non-endemic countries, is a significant concern. Furthermore, the substantial genetic variability of these organisms will likely render currently utilized importation diagnostic tests unable to detect all equine Theileria spp. To this end, more complete characterization of these diverse parasites is critical to the continued global control of equine theileriosis. This review discusses current knowledge of equine Theileria spp. in this context, and highlights new opportunities and challenges for workers in this field.